Pengaruh Plant Growth Promoting Rhizobacteria (PGPR) terhadap Pertumbuhan dan Hasil Tanaman Kacang hijau (Vigna radiata L.) - Wini Syahira; Tri Pamujiasih; Srie Juli Rachmawatie (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
Plant Growth Promoting Rhizobacteria (PGPR) is a colony of bacteri on roots that plays an important role in plant growth. This research was conducted in Jaban RT 03 RW 06, Segaran, Delanggu, Klaten, Central Java, in August-October 2020. The method used a factorial Completely Randomized Design (CRD) with three replications, namely variety (V) consist of 2 levels (varieties), namely: V1=Vima-1 and V2 = Vima-2. PGPR (D) consist of 3 stages (dosage), namely D1 = 5 cc/liter dose; D2 = Dosage 10 cc/liter; and D3 = Dosage 15 cc/liter. The data were analyzed using analysis of variance followed by the DMRT test if there were significant and very significant differences between treatments or treatment interactions. The results showed that the interaction of PGPR treatment and varieties had a significant effect on plant height and number of pods per plant and had a very significant effect on the weight of 100 seeds. However, the treatment interactions have no significant effect on seed weight per plant and root volume.